2017
DOI: 10.26420/austinpediatr.2017.1057
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Public Health Nurses with Breastfeeding Interventions for Late Preterm Infants

Abstract: Late preterm infants often experience feeding difficulty post discharge from hospital. While breast milk is especially important for late preterm infants, they have lower exclusive breastfeeding rates than full term infants. This is because mothers of late preterm infants often do not receive sufficient amount of breastfeeding support in the postpartum period. Furthermore, in the Canadian context, guidelines do not exist for health care providers to use to assist them in providing breastfeeding support for mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(270 reference statements)
0
1
0
Order By: Relevance
“…Dosani and Currie (2017) highlighted that there are many unique breastfeeding challenges with late preterm infants and reinforced that breastfeeding support is crucial to ensure success. Further, Gerhardsson et al (2018) found that length of hospital stay was inversely correlated with BSE in mothers of late preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Dosani and Currie (2017) highlighted that there are many unique breastfeeding challenges with late preterm infants and reinforced that breastfeeding support is crucial to ensure success. Further, Gerhardsson et al (2018) found that length of hospital stay was inversely correlated with BSE in mothers of late preterm infants.…”
Section: Discussionmentioning
confidence: 99%